Recycling method of waste lithium iron phosphate batteries
Through electrolysis and titration and impregnation treatment of sodium salt solution, the problems of pollution and high energy consumption in lithium iron phosphate battery recycling were solved, and high-performance carbon-coated sodium iron phosphate lithium was produced, achieving efficient recycling and regeneration of lithium iron phosphate batteries. .
Patent Information
- Application Number
- CN202310601250.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The existing lithium iron phosphate battery recycling methods have problems such as high pollution, high energy consumption, high wet recovery costs and high carbon content of direct regeneration methods, and cannot effectively recover and regenerate valuable metals from lithium iron phosphate batteries.
The positive electrode material and current collector were separated by electrolytic method, and carbon-coated lithium iron phosphate was prepared by titration impregnation and heat treatment of sodium salt solution, which simplified the process, reduced energy consumption, and improved recovery and electrochemical performance.
It realizes efficient separation and regeneration of the cathode material of lithium iron phosphate battery, reduces process pollution and energy consumption, and improves the electrochemical performance and market applicability of the recycled products.
Smart Images

Figure CN116435640B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery recycling, and in particular to a method for recycling waste lithium iron phosphate batteries. Background Art
[0002] Large-capacity, long-life, high-safety, and low-cost energy storage devices are the core units urgently needed to realize the application of renewable energy, the construction of smart grids, and the development of electric vehicles. As an efficient energy storage device, lithium-ion batteries are entering a stage of rapid development. Lithium iron phosphate materials have the advantages of abundant and easy-to-obtain raw materials, low dependence on external resources, and environmental friendliness. In addition, the stable lattice structure gives it a relatively safe and long-cycle gene, which is an important guarantee for the healthy development of new energy vehicles and renewable energy in the future. With technological progress, the optimization of battery pack system design, such as blade, CTP, JTM and other integrated manufacturing technology innovations, effectively make up for the energy density shortcomings of lithium iron phosphate materials. In 2020, lithium iron phosphate batteries entered a stage of rapid development, and the market size is getting bigger and bigger. There is a large market space in energy storage, 5G base stations, new energy vehicles, and renewable energy grid connection, and it is expected to occupy a dominant position in the market for a long time in the future.
[0003] However, after hundreds of charge and discharge cycles, the internal structure of lithium iron phosphate batteries will undergo irreversible changes, which will cause the blockage of lithium ion channels and lead to the deactivation of the battery. At present, the average service life of lithium iron phosphate batteries is 3 to 8 years. Due to the early commercial application of lithium iron phosphate batteries, the explosion period of lithium iron phosphate battery retirement has begun. It is estimated that by 2025, nearly 100GWh of lithium iron phosphate waste batteries will be generated in China alone. In the long run, the amount of lithium iron phosphate retired will be even larger, and such a large amount of retired batteries will pose serious challenges to the recycling and reuse of lithium iron phosphate waste batteries and materials. Untreated waste power battery electrolytes are very easy to react in the environment and cause pollution to soil, water sources, etc. Recycling metal elements such as lithium resources in waste lithium-ion batteries can reduce resource waste and better alleviate the pressure on lithium resources. At present, the objects of lithium-ion battery recycling worldwide are mainly ternary lithium-ion batteries containing precious metals such as cobalt. The economic value of lithium iron phosphate battery recycling is low. There are few companies engaged in lithium iron phosphate waste recycling business, and most of them are in the experimental research stage.
[0004] At present, the main recycling methods for waste lithium iron phosphate battery positive electrode materials include pyrometallurgical recycling, wet recycling and direct regeneration. Among them, pyrometallurgical recycling uses external force to forcefully crush the discarded lithium iron phosphate batteries, and calcines the screened powder at high temperature. The carbon, organic matter and related binders in the powder are burned by high temperature, and finally valuable metals and metal oxides are obtained. Subsequently, mechanical sorting is carried out to orderly recycle different metals and their oxides. The advantage of pyrometallurgical recycling is that the process is developed early and the technical route is mature, so it is widely used and has a high recovery rate. However, due to the low technical content in the process route, its simple pyrometallurgical calcination process is often insufficiently recycled, accompanied by a lot of pollution, and huge energy consumption. At the same time, the recovery value of lithium iron phosphate materials is low, which is not suitable for large-scale application. Wet recovery of valuable metals is to use hydrometallurgy to recover the valuable metal elements in the positive electrode materials of waste lithium iron phosphate batteries. Waste lithium iron phosphate positive electrode materials are leached with a lixiviant, and elements such as lithium, iron and phosphorus enter the solution in the form of ions. After the leaching solution is purified by impurities removal, lithium and iron elements are separated and recovered. Lithium is generally recovered in the form of lithium carbonate and lithium phosphate, while iron is generally recovered in the form of iron phosphate and iron hydroxide. The wet full-component leaching process can achieve full-component recovery of waste lithium iron phosphate positive electrode materials, and has the advantages of high metal recovery rate and high purity of recovered products; but because the structure of olivine-type lithium iron phosphate is very stable, strong acid needs to be added to destroy its structure and the acid consumption is usually large, and a large amount of alkali should be added in the subsequent steps for neutralization, resulting in high recovery costs; in addition, the recovery process has problems such as generating a large amount of waste liquid, a long process flow and more complicated operations. For example, CN114349030A discloses a comprehensive wet recycling method for waste lithium iron phosphate positive plates, which comprises crushing and grading the positive plates disassembled from waste lithium iron phosphate batteries to obtain positive electrode powder and aluminum chips; acid leaching the positive electrode powder, adding iron powder to react, obtaining acid leaching filtrate and acid leaching residue, and the acid leaching residue is used to prepare crude carbon powder; adding Al removal agent to the acid leaching filtrate and filtering to obtain refined acid leaching filtrate and Al removal residue; adding a mixed solution of hydrogen peroxide and ammonia water to the refined acid leaching filtrate after adjusting the iron-phosphorus ratio, filtering and washing to obtain a crude iron phosphate filter cake and a Li-containing filtrate; treating the crude iron phosphate to obtain an anhydrous iron phosphate finished product; Ammonia water and (NH4)2CO3 are added to the Li-containing filtrate, filtered and washed to obtain impurity-free residue and refined Li-containing filtrate, the refined Li-containing filtrate is concentrated, ammonia water is added to adjust the pH, ((NH4)2CO3 is added for filtration to obtain crude Li2CO3, and this method can realize the recycling of all elements of iron, phosphorus, lithium, aluminum foil and carbon. The direct regeneration method refers to the process of stripping the active material from the positive electrode sheet and regenerating it in a high-temperature protective gas by adding or not adding other reagents, that is, restoring the electrochemical properties of the failed lithium iron phosphate material by supplementing the missing substances. The direct regeneration method has the advantages of short process and simple operation.However, the regeneration methods currently used cannot remove the influence of carbon on the positive electrode material, resulting in a high carbon content in the regenerated lithium iron phosphate positive electrode material, and a decrease in the discharge specific capacity and volume energy density. At the same time, it was found that the lithium iron phosphate positive electrode material obtained by direct regeneration is generally difficult to meet commercial needs, especially the discharge specific capacity at high rates is low, which may be due to the fact that the lattice of the waste positive electrode material is not completely destroyed, which is not conducive to the regeneration process. CN115472825A discloses a preparation process for a high-stability sodium ion battery positive electrode material, which uses lithium iron phosphate as a positive electrode, lithium salt to make an electrolyte solution, and a carbon material as a negative electrode, and connects a power supply for constant current charging. In the liquid phase solution, lithium ions migrate out of the positive electrode, and after charging, an olivine-structured iron phosphate is obtained; then the iron phosphate is evenly mixed with an organic sodium salt, ball milled, and calcined at 200 to 400 ° C in a protective atmosphere, so that the sodium ions in the organic sodium salt migrate into the iron phosphate to obtain a sodium iron phosphate positive electrode material.
[0005] It can be seen that the existing methods for recovering valuable metals from waste lithium iron phosphate batteries still have a lot to be improved. In order to facilitate later use, it is necessary to develop a simple and easy method that can realize the recycling of waste lithium iron phosphate batteries. Summary of the invention
[0006] The purpose of the present invention is to provide a method for recycling waste lithium iron phosphate batteries to solve various problems encountered in the current recycling process of lithium iron phosphate battery positive electrode materials.
[0007] The present invention provides a method for recycling waste lithium iron phosphate batteries, comprising the following steps:
[0008] Step 1, discharge and dismantle the used lithium iron phosphate battery:
[0009] The used lithium iron phosphate batteries are completely discharged, and then mechanically disassembled, the outer shell is removed, the positive electrode sheet, the negative electrode sheet and the separator are separated, and the positive electrode sheet is cut;
[0010] Step 2, separation of electrode material and current collector:
[0011] Separating the positive electrode material from the current collector to obtain a positive electrode material mixture and an aluminum foil, wherein the positive electrode material mixture includes lithium iron phosphate, a conductive agent, and a binder;
[0012] Step 3, obtaining the content of the main elements in the positive electrode material mixture:
[0013] Take a positive electrode material mixture with a mass of m and test the contents of the elements Li, Fe and P therein, and the amounts of the substances are measured to be a, b and d respectively;
[0014] Step 4, impregnation of positive electrode material mixture:
[0015] At room temperature and pressure, a positive electrode material mixture with a mass of M is crushed and uniformly mixed with lithium carbonate powder, and then titrated and impregnated with an aqueous solution of sodium salt, and the volume of the sodium salt mixed solution consumed after the titration is V, to obtain an impregnated positive electrode material mixture;
[0016] Wherein, the amount of substance of lithium carbonate powder is n, the amount of substance concentration of sodium ions in sodium salt is c, and it satisfies:
[0017]
[0018]
[0019] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0020] The impregnated positive electrode material mixture obtained in step 4 is then used to obtain carbon-coated sodium lithium iron phosphate.
[0021] As a preferred embodiment of the present invention, in step 1, completely discharging the waste lithium iron phosphate battery is achieved by immersing it in a saturated NaCl solution for 3 to 10 hours.
[0022] As a preferred embodiment of the present invention, in step 2, the electrode material and the current collector are separated by electrolysis; specifically, an electrolytic cell containing saturated nitrate as a supporting electrolyte is prepared, and the electrode sheet is cut into pieces of 0.1 cm 2 ~400cm 2 Place two positive electrode sheets at the two poles of the electrolytic cell and apply periodic square wave current or triangular wave current at the two poles with a current density of 1 mA / cm 2 ~500mA / cm 2 ; After the electrode material is electrolyzed until it falls off the surface of the current collector, the current collector and the electrode material are taken out of the electrolytic cell to separate the current collector and the electrode material.
[0023] As a preferred embodiment of the present invention, in step 3, the content of the main elements in the positive electrode material mixture is obtained by randomly selecting multiple positive electrode material mixture samples from the same batch, weighing samples with a mass of m respectively and detecting the content of the elements Li, Fe and P therein respectively, and performing weighted average calculation on the contents obtained from the randomly selected multiple samples to obtain the amounts of substances of the elements Li, Fe and P as a, b and d respectively.
[0024] As a preferred embodiment of the present invention, in step 4, the positive electrode material mixture is pulverized by ball milling. Preferably, the ball milling is performed for 3 to 8 hours at a ball mill speed of 200-400 rpm. The mixing is achieved by stirring, preferably by magnetic stirring.
[0025] As a preferred embodiment of the present invention, in step 4, when the immersion is complete, the volume V of the sodium salt aqueous solution is measured by the following method: starting from the first drop of the sodium salt aqueous solution, the measurement is added drop by drop until another drop of the sodium salt aqueous solution is added and then crushed and mixed evenly with the lithium carbonate powder, and the positive electrode material mixture becomes a paste. At this time, the total volume of the sodium salt aqueous solution added is V.
[0026] As a preferred embodiment of the present invention, in step 4, the sodium salt solution titration impregnation is incomplete impregnation, complete impregnation or excessive impregnation.
[0027] As a preferred embodiment of the present invention, in step 4, after the positive electrode material mixture is prepared after impregnation, an ultrasonic treatment step is also included; further, the ultrasonic treatment conditions are an ultrasonic frequency of 20-50kHz and a stirring speed of 80-300 revolutions per minute. The sodium salt aqueous solution is impregnated to increase the contact surface between the sodium and the positive electrode material mixture, and the ultrasonic dispersion further improves the mixing uniformity of the sodium ions and the positive electrode material mixture, thereby improving the uniformity of the final regenerated positive electrode material and making the regenerated positive electrode material have good electrochemical properties.
[0028] As a preferred embodiment of the present invention, in step 4, the sodium salt is sodium carbonate, sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0029] As a preferred embodiment of the present invention, in step 4, the molar concentration c of sodium ions in the sodium salt also satisfies:
[0030]
[0031] As a preferred embodiment of the present invention, in the step 5, the heat treatment conditions are 650°C-750°C, 1-4h, and the atmosphere is N2 or Ar; further preferably, the heat treatment temperature can be selected as 650°C, 655°C, 660°C, 665°C, 670°C, 675°C, 680°C, 685°C, 690°C, 695°C, 700°C, 705°C, 710°C, 715°C, 720°C, 725°C, 730°C, 735°C, 740°C, 745°C, 750°C; further preferably, the heat treatment time can be selected as 1h, 1.25h, 1.5h, 1.75h, 2h, 2.25h, 2.5h, 2.75h, 3h.
[0032] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0033] First, unlike the existing mainstream pyrometallurgical recycling and wet recycling of waste lithium iron phosphate batteries, the present invention does not require conventional strong mechanical separation or acid leaching and alkali leaching. In the process of separating the positive electrode material from the current collector, an electrolysis method with simple operation, low energy consumption and less pollution is adopted, making the initial separation step more convenient and environmentally friendly.
[0034] Second, compared with the existing direct regeneration method, the present invention obtains the contents of lithium, iron and phosphorus in the mixture of lithium iron phosphate positive electrode materials to be recycled by sampling, determines the amount of lithium to be added according to the contents of the three elements, and creatively further introduces sodium to dope and modify the lithium iron phosphate to be recycled. This, on the one hand, makes lithium surplus, facilitates heat treatment and the loss of lithium during the subsequent circulation process during use, and on the other hand, improves the initial capacity and cycle performance of the battery by introducing an appropriate amount of sodium.
[0035] Third, the present invention limits the specific concentration range of lithium carbonate and sodium salt according to the content of each element in the lithium iron phosphate to be recovered, and maintains a fixed ratio of lithium salt and sodium salt in the mixed impregnation solution, thereby obtaining carbon-coated sodium-doped lithium iron phosphate with high initial capacity and good cycle performance; the precise definition of the specific introduction amount of lithium and sodium ensures the uniformity of the regenerated positive electrode material and the stability of the electrochemical performance.
[0036] Fourthly, the heat treatment process of the present invention ensures good carbon coating, so that the regenerated positive electrode material has good conductivity, further promoting the performance of the positive electrode material, and in this way, the conductive agent and the binder are fully utilized, saving resources.
[0037] Fifth, the overall process of the present invention fully considers environmental protection and ease of operation in all links, has low energy consumption, and the prepared positive electrode material has good performance and is suitable for use in mid-to-high-end lithium battery applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0039] Figure 1 The present invention is a flow chart of a method for recycling waste lithium iron phosphate batteries provided in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0040] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0041] It should be noted that the terms "including" and "having" in the embodiments of the present application and any variations thereof are intended to cover non-exclusive inclusions.
[0042] Examples 1-16
[0043] Examples 1-16 use the same batch of waste lithium iron phosphate batteries, and their recycling methods all include steps 1-3:
[0044] Step 1, discharge and dismantle the used lithium iron phosphate battery:
[0045] The waste lithium iron phosphate battery is completely discharged. Specifically, the waste lithium iron phosphate battery is completely discharged by soaking it in a saturated NaCl solution for 3 to 10 hours, and then mechanically dismantling it, removing the outer shell, separating the positive electrode sheet, the negative electrode sheet and the separator, and cutting the positive electrode sheet;
[0046] Step 2, separation of electrode material and current collector:
[0047] Separating the positive electrode material from the current collector to obtain a positive electrode material mixture and an aluminum foil, wherein the positive electrode material mixture includes lithium iron phosphate, a conductive agent, and a binder;
[0048] Specifically, the electrode material and the current collector are separated by electrolysis; the process includes preparing an electrolytic cell filled with saturated nitrate as a supporting electrolyte, cutting the electrode sheet into pieces of 0.1 cm 2 ~400cm 2 Small pieces, preferably cut into 20×5 cm 2 The size of the small piece is not limited to this, and it can be cut according to the situation of the electrolytic solution. The two positive electrode pieces are placed at the two poles of the electrolytic cell, and a periodically changing square wave current or triangular wave current is applied to the two poles. The current density is 1mA / cm 2 ~500mA / cm 2 ; After the electrode material is electrolyzed until it falls off the surface of the current collector, the current collector and the electrode material are removed from the electrolytic cell to separate the current collector and the positive electrode material mixture.
[0049] In addition, similarly, the negative electrode sheet can also be electrolytically separated by a similar method, and the copper foil can be recovered for recycling.
[0050] The electrolysis method in step 3 is used to separate the electrode material and the current collector. The reaction is milder and does not involve extremely high temperatures or produce large amounts of gas. The method is simple, effective, environmentally friendly and has low energy consumption.
[0051] Step 3, obtaining the content of the main elements in the positive electrode material mixture:
[0052] Randomly select 5 positive electrode material mixtures obtained after steps 1-2 of different batteries in the batch, and respectively measure the amount of Li, Fe and P in the positive electrode material mixture with a mass of m=10g. The average amount of Li, Fe and P in the positive electrode material mixture with a mass of m=10g of the 5 samples is obtained by weighted average, and the average amount of Li, Fe and P is a=0.059 mol, b=0.062 mol and d=0.064 mol;
[0053] Example 1
[0054] Step 4, impregnation of positive electrode material mixture:
[0055] At room temperature and pressure, a positive electrode material mixture with a mass of M=500g is crushed and evenly mixed with lithium carbonate powder, and then titrated and impregnated with sodium carbonate aqueous solution. The volume of sodium carbonate aqueous solution consumed after the titration is V=0.34L, and the impregnated positive electrode material mixture is obtained; the sodium carbonate can also be replaced by sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0056] The amount of lithium carbonate powder is n = 0.42 mol, and the amount of sodium ions in sodium carbonate is c = 1.05 mol / L.
[0057] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0058] The impregnated positive electrode material mixture obtained in step 4 is used to obtain carbon-coated sodium lithium iron phosphate, wherein the heat treatment is carried out under Ar atmosphere at 690° C. for 2 hours.
[0059] Embodiment 2-4
[0060] Compared with step 4-5 of example 1, step 4-5 of example 2-4 is the same except that n is 0.44 mol, 0.46 mol and 0.48 mol respectively.
[0061] Embodiment 5-7
[0062] Compared with step 4-5 of embodiment 3, step 4-5 of embodiment 5-7 is the same as step 4-5 of embodiment 3, except that V is 0.3L, 0.32L and 0.36L respectively.
[0063] Example 8
[0064] Step 4, impregnation of positive electrode material mixture:
[0065] At room temperature and pressure, a positive electrode material mixture with a mass of M=500g is crushed and evenly mixed with lithium carbonate powder, and then titrated and impregnated with a sodium carbonate aqueous solution. The volume of the sodium carbonate aqueous solution consumed after the titration is V=0.45L, and the impregnated positive electrode material mixture is obtained; the sodium carbonate can also be replaced by sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0066] The amount of lithium carbonate powder is n = 0.46 mol, and the amount of sodium ions in sodium carbonate is c = 0.7 mol / L.
[0067] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0068] The impregnated positive electrode material mixture obtained in step 4 is used to obtain carbon-coated sodium lithium iron phosphate, wherein the heat treatment is carried out under Ar atmosphere at 690° C. for 2 hours.
[0069] Examples 9-11
[0070] Compared with Step 4-5 of Example 8, Step 4-5 of Example 9-11 is the same as Step 4-5 of Example 8, except that V is 0.48L, 0.51L and 0.54L respectively.
[0071] Examples 12-16
[0072] Compared with step 4-5 of example 10, steps 4-5 of examples 12-16 are the same except that the heating temperature and time correspond to: 650°C for 3h, 675°C for 2.5h, 700°C for 2h, 725°C for 1.5h, and 750°C for 1h.
[0073] Comparative Example 1
[0074] Step 4, impregnation of positive electrode material mixture:
[0075] At room temperature and pressure, a positive electrode material mixture with a mass of M=500g is crushed and evenly mixed with lithium carbonate powder, and then titrated and impregnated with sodium carbonate aqueous solution. The volume of sodium carbonate aqueous solution consumed after the titration is V=0.51L, and the impregnated positive electrode material mixture is obtained; the sodium carbonate can also be replaced by sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0076] The amount of lithium carbonate powder is n = 0.38 mol, and the amount of sodium ions in sodium carbonate is c = 0.7 mol / L.
[0077] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0078] The impregnated positive electrode material mixture obtained in step 4 is used to obtain carbon-coated sodium lithium iron phosphate, wherein the heat treatment is carried out under Ar atmosphere at 690° C. for 2 hours.
[0079] Comparative Example 2
[0080] Steps 4-5 of Comparative Example 2 are the same as Steps 4-5 of Comparative Example 1 except that n is 0.52 mol.
[0081] Comparative Example 3
[0082] Step 4, impregnation of positive electrode material mixture:
[0083] At room temperature and pressure, a positive electrode material mixture with a mass of M=500g is crushed and evenly mixed with lithium carbonate powder, and then titrated and impregnated with sodium carbonate aqueous solution. The volume of sodium carbonate aqueous solution consumed after the titration is V=0.42L, and the impregnated positive electrode material mixture is obtained; the sodium carbonate can also be replaced by sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0084] The amount of lithium carbonate powder is n = 0.46 mol, and the amount of sodium ions in sodium carbonate is c = 0.7 mol / L.
[0085] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0086] The impregnated positive electrode material mixture obtained in step 4 is used to obtain carbon-coated sodium lithium iron phosphate, wherein the heat treatment is carried out under Ar atmosphere at 690° C. for 2 hours.
[0087] Comparative Example 4
[0088] Steps 4-5 of Comparative Example 4 are the same as Steps 4-5 of Comparative Example 3 except that V is 0.57L.
[0089] Comparative Example 5
[0090] Step 4, impregnation of positive electrode material mixture:
[0091] At room temperature and pressure, a positive electrode material mixture with a mass of M=500g is crushed and evenly mixed with lithium carbonate powder, and then titrated and impregnated with sodium carbonate aqueous solution. The volume of sodium carbonate aqueous solution consumed after the titration is V=0.51L, and the impregnated positive electrode material mixture is obtained; the sodium carbonate can also be replaced by sodium bicarbonate, sodium hypochlorite or sodium chloride.
[0092] The amount of lithium carbonate powder is n = 0.46 mol, and the amount of sodium ions in sodium carbonate is c = 0.7 mol / L.
[0093] Step 5, heat treatment of the positive electrode material mixture after impregnation:
[0094] The impregnated positive electrode material mixture obtained in step 4 is used to obtain carbon-coated sodium lithium iron phosphate, wherein the heat treatment is carried out under Ar atmosphere at 550° C. for 4 hours.
[0095] Comparative Examples 6-8
[0096] Compared with step 4-5 of comparative example 5, steps 4-5 of comparative example 6-8 are the same as those of step 4-5 of comparative example 5, except that the heating temperature and time correspond to: 600°C for 3.5h, 775°C for 1h, and 800°C for 0.75h.
[0097] test
[0098] The carbon-coated sodium lithium iron phosphate of Examples 1-16 and Comparative Examples 1-8 were used as positive electrode active materials to make button batteries for comparative study of electrochemical performance. Button battery production: Lithium iron phosphate active material, conductive carbon black, and PVDF were mixed in a mass ratio of 90:7:3 to form a slurry, which was coated on aluminum foil and baked at 120°C for 8 hours. The slurry was then rolled and cut to prepare small circular pole pieces for button battery production. The button battery was assembled in a glove box, and the glove box conditions were that the water and oxygen content was less than or equal to 0.01ppm, and the electrolyte was 1.0MLiPF6in EC:DMC:DEC=1:1:1Vol%. The conductivity of the battery was tested, and the test conditions for the battery cycle performance were: the charge and discharge voltage range was 2.5-4.2V (relative Li+ / Li), the ambient temperature was 25°C, 0.2C charge and discharge was used, and the capacity retention rate was tested at 1C for 100 cycles, and the battery performance was obtained, as shown in Tables 1 and 2.
[0099] Table 1: Electrochemical performance test results of Examples 1-16
[0100] 0.2C discharge capacity Capacity retention rate 0.2C discharge capacity Capacity retention rate Example 1 151.9mAh / g 97.3% Example 9 154.1mAh / g 98.5% Example 2 153mAh / g 97.7% Example 10 155.6mAh / g 98.8% Example 3 153.2mAh / g 98.1% Embodiment 11 154.2mAh / g 98.1% Example 4 152.9mAh / g 97.9% Example 12 153.8mAh / g 98% Example 5 152.6mAh / g 98.7% Embodiment 13 154.9mAh / g 98.3% Example 6 152.8mAh / g 97.6% Embodiment 14 155.5mAh / g 98.6% Example 7 152.1mAh / g 97.9% Embodiment 15 155.1mAh / g 98.3% Example 8 153.9mAh / g 98.2% Example 16 155.3mAh / g 98.2%
[0101] Table 2: Electrochemical performance test results of Comparative Examples 1-8
[0102] 0.2C discharge capacity Capacity retention rate 0.2C discharge capacity Capacity retention rate Comparative Example 1 136.3mAh / g 95.3% Comparative Example 5 116.3mAh / g 88.3% Comparative Example 2 135.4mAh / g 95.2% Comparative Example 6 125.4mAh / g 90.2% Comparative Example 3 138.4mAh / g 95% Comparative Example 7 121.1mAh / g 89.8% Comparative Example 4 137.3mAh / g 91.2% Comparative Example 8 117.5mAh / g 87.6%
[0103] It is easy to find from the test results shown in Table 1 that when the relationship between n, c, and V satisfies
[0104]
[0105] When the three relationship equations are obtained, the carbon-coated sodium lithium iron phosphate directly prepared from waste lithium iron phosphate batteries shows good initial capacity and excellent cycle performance, wherein the 0.2C discharge capacity is 151 mAh / g, and the capacity retention rate is above 97%. This is because n, c, and V are closely related to the contents of Li, Fe, and P elements in the cathode material mixture in the disassembled and separated waste batteries; at the same time, since the present invention directly utilizes a conductive agent and a binder to carbon-coat the sodium lithium iron phosphate under an inert atmosphere, the conductivity of the recycled carbon-coated sodium lithium iron phosphate is improved, which also promotes the improvement of capacity and cycle performance.
[0106] By comparing the test results shown in Table 1 and Table 2, it is not difficult to find that when the relationship between n, c, and V does not satisfy the three equations, the carbon-coated sodium iron phosphate directly prepared from waste lithium iron phosphate batteries has good cycle performance, but the initial capacity declines seriously.
[0107] Specifically, the test results shown in Table 1 show that in Examples 1-4, as the amount of lithium supplemented substance n gradually increases from 0.42 mol to 0.48 mol, the 0.2C discharge capacity of the button cell shows a trend of first increasing and then decreasing, reaching a peak value when n=0.46 mol, and the capacity retention rate is also the highest here. This is mainly due to two reasons. First, as the amount of excess lithium ions introduced by lithium carbonate increases, the grains of the recycled carbon-coated sodium iron lithium phosphate will be refined, relieving the sintering and fusion between the grains, and its discharge performance will increase, thereby improving both the initial capacity and the cycle performance. However, as the amount of lithium carbonate further increases, the increase in the excess degree will lead to the generation of inactive lithium phosphate phases, so the capacity and cycle performance of Example 4 are slightly reduced. Combining Example 10 in Table 1 and Comparative Examples 1-2 in Table 2, it can be seen that insufficient and excessive lithium carbonate both lead to a decrease in initial capacity and cycle performance.
[0108] The test results shown in Table 1 show that the amount of sodium ions introduced gradually increases in the order of Examples 5, 6, 3, and 7. Similarly, the amount of sodium ions introduced in Examples 8-11 also gradually increases. By comparison, it is found that when cV=0.357 mol, the capacity and cycle performance of the button battery reach a peak value. At the same time, combined with the results of Comparative Examples 3-4 in Table 2, similar results are shown, which show that too much or too little sodium ions are not conducive to improving the performance of recycled positive electrode materials. Although sodium ions are alkali metal particles similar to lithium ions, they are very different in size, and thus have different mechanisms. It is speculated that during sintering, too much sodium occupies the position of Fe, resulting in instability or collapse of the framework part in the spinel structure, resulting in reduced capacity and cycle performance. In addition, by comparing Examples 5, 6, 3, and 7 with Examples 8-11 one by one, it can be seen that the cV values of 5 and 8, 6 and 9, 3 and 10, and 7 and 11 are the same, but because c is different, the V required for impregnation is different. The smaller c is, the larger V is, and the more complete the impregnation of the positive electrode material mixture is. After sintering, the lithium and sodium elements react with the main material more evenly and fully, thereby promoting the improvement of capacity and cycle performance.
[0109] The test results shown in Table 1 show that different heat treatment temperatures and corresponding times are given in Examples 10, 12-16. The results show that the insulation time can be increased when the temperature is low, and the insulation time can be reduced when the temperature is high, and basically good electrical performance can be achieved. However, combined with Comparative Examples 5-8 in Table 2, the electrochemical performance is greatly reduced even if the insulation time is adjusted beyond the temperature range of 650℃-750℃. This is mainly because the temperature is too low to meet the reaction requirements, and the temperature is too high. The phase change reaction is complicated and the carbon coating effect is greatly reduced. Therefore, the heat treatment temperature should be limited to 650℃-750℃, and the insulation time is 1-3h. Heat treatment of the impregnated positive electrode material mixture in an inert atmosphere.
[0110] Examples 17-20
[0111] Examples 17-20 respectively use waste lithium iron phosphate batteries from different batches than those of Examples 1-16. The preparation process and test method are similar to those of Examples 1-16, and the various parameters and electrochemical properties are shown in Table 3.
[0112] Table 3: Electrochemical performance test results of Examples 17-20
[0113]
[0114]
[0115] According to Table 3, Examples 17-20 are respectively four different batches of waste lithium iron phosphate batteries different from Examples 1-16. The materials and process parameters selected in the preparation process of the method of the present invention are used to limit the contents of Li, Fe and P elements in the positive electrode material mixture to three relational equations, and the regenerated positive electrode materials with excellent electrochemical properties are also obtained. The method of the present invention is suitable for recycling positive electrode materials of various types of waste lithium iron phosphate batteries, and the obtained regenerated positive electrode materials are suitable for mid-to-high-end application scenarios.
[0116] The above is a detailed description of a method for recycling waste lithium iron phosphate batteries disclosed in the embodiment of the present application. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A method for recycling waste lithium iron phosphate batteries, characterized in that: The steps include: Step 1, discharge and dismantle the used lithium iron phosphate battery: The used lithium iron phosphate batteries are completely discharged, and then mechanically disassembled, the outer shell is removed, the positive electrode sheet, the negative electrode sheet and the separator are separated, and the positive electrode sheet is cut; Step 2, separation of electrode material and current collector: Separating the positive electrode material from the current collector to obtain a positive electrode material mixture and an aluminum foil, wherein the positive electrode material mixture includes lithium iron phosphate, a conductive agent, and a binder; Step 3, obtaining the content of the main elements in the positive electrode material mixture: Take a positive electrode material mixture with a mass of m and test the contents of the elements Li, Fe and P therein, and the amounts of the substances are measured to be a, b and d respectively; Step 4, impregnation of positive electrode material mixture: At room temperature and pressure, a positive electrode material mixture with a mass of M is crushed and uniformly mixed with lithium carbonate powder, and then titrated and impregnated with an aqueous solution of sodium salt, and the volume of the sodium salt mixed solution consumed after the titration is V, to obtain an impregnated positive electrode material mixture; Wherein, the amount of substance of lithium carbonate powder is n, the amount of substance concentration of sodium ions in sodium salt is c, and it satisfies: Step 5, heat treatment of the positive electrode material mixture after impregnation: The impregnated positive electrode material mixture obtained in step 4 is heat-treated to obtain carbon-coated sodium lithium iron phosphate; wherein the heat treatment conditions are 650° C.-750° C., 1-3 h, and the atmosphere is N2 or Ar.
2. The method for recycling waste lithium iron phosphate batteries according to claim 1, characterized in that: In the step 1, the waste lithium iron phosphate battery is completely discharged by immersing it in a saturated NaCl solution for 3 to 10 hours.
3. The method for recycling waste lithium iron phosphate batteries according to claim 1, characterized in that: In step 2, the electrode material and the current collector are separated by electrolysis; specifically, an electrolytic cell containing saturated nitrate as a supporting electrolyte is prepared, and the electrode pieces are cut into pieces with a size of 0.1 cm 2 ~400cm 2 Place two positive electrode sheets at the two poles of the electrolytic cell and apply periodic square wave current or triangular wave current at the two poles with a current density of 1 mA / cm 2 ~500mA / cm 2 ; After the electrode material is electrolyzed until it falls off the surface of the current collector, the current collector and the electrode material are taken out of the electrolytic cell to separate the current collector and the electrode material.
4. The method for recycling waste lithium iron phosphate batteries according to claim 1, characterized in that: In step 4, the sodium salt solution titration impregnation is incomplete impregnation, complete impregnation or excessive impregnation.
5. The method for recycling waste lithium iron phosphate batteries according to claim 1, characterized in that: In step 4, after the positive electrode material mixture is prepared after impregnation, an ultrasonic treatment step is also included.
6. The method for recycling waste lithium iron phosphate batteries according to claim 5, characterized in that: In step 4, the sodium salt is sodium carbonate, sodium bicarbonate, sodium hypochlorite or sodium chloride.
Citation Information
Patent Citations
Comprehensive wet recycling method of lithium iron phosphate waste positive plate
CN114349030A
Preparation process of high-stability sodium ion battery positive electrode material and sodium ion battery
CN115472825A
Doping and dipping coating synchronously modified polycrystalline positive electrode material and solid-phase preparation method and application thereof
CN113130877A
Direct regeneration method of waste lithium iron phosphate positive electrode material
CN114744315A
Method for recovering metal
KR1020120045701A
